Pertumbuhan dan Produksi Jagung Manis dengan Aplikasi Pupuk Kandang Sapi dan Pupuk NPK (Zea mays L. Saccharata sturt.) - Syahputra, Amanda; Zulfida, Ida; Miyarnis, Miyarnis (JURNAL AGROPLASMA, 2024)
This study aimed to evaluate the effect of cow manure and NPK fertilizer application on the growth and production of sweet corn (Zea mays L. Saccharata Sturt). The study was conducted from June to October 2024 at the experimental garden of the Faculty of Agriculture, Universitas Pembinaan Masyarakat Indonesia, Medan Amplas. A Randomized Block Design (RBD) was used, with two factors studied: cow manure application (0%, 25%, and 50%) and NPK fertilizer (0 g, 0.5 g, and 1 g per plant). Each treatment was repeated three times, resulting in a total of nine experimental units. The results showed that cow manure application had a significant effect on plant height but did not affect the number of leaves, cob length, or cob weight per plot or per sample. Meanwhile, NPK fertilizer application did not show a significant effect on all parameters measured. The interaction between cow manure and NPK significantly affected the number of leaves at 6 WAP but did not affect plant height at 2 WAP, 4 WAP, and 6 WAP, as well as on cob length, cob weight per plot, and cob weight per sample. This study provides insight into the effectiveness of using organic and inorganic fertilizers in increasing sweet corn productivity. Keywords: sweet corn, cow manure, npk fertilizer